Statistical Learning of Two Artificial Languages Presented Successively: How Conscious? - Franco, Ana; Cleeremans, Axel; Destrebecqz, Arnaud (Frontiers in Psychology, 2011)
Statistical learning is assumed to occur automatically and implicitly, but little is known about the extent to which the representations acquired over training are available to conscious awareness. In this study, we focus whether the knowledge acquired in a statistical learning situation is conscious or not. Here, participants were first exposed to an artificial language presented auditorily. Immediately thereafter, they were exposed to a second artificial language. . Both languages were composed of the same corpus of syllables and differed only in the transitional probabilities between the latter. We first controlled that both languages were equally learnable (Experiment 1) and that participants could learn the two languages and differentiate between them (Experiment 2). In Experiment 3, we used an adaptation of the Process Dissociation Procedure (Jacoby, 1991) to explore whether knowledge of each language was consciously accessible and manipulable. Results suggest that statistical information can be used to parse and differentiate between two different artificial languages, and that the resulting representations are conscious.